Rhematization by means of non-canonical structures - Machurková, Anna (Univerzita Pardubice, 2012)
The purpose of this paper is to analyse the use of non-canonical structures in academic style. In the theoretical part, principles of English word order are discussed. Furthermore, the paper focuses on the description of non-canonical structures as the means of rearrangement of the canonical word order. The analytical part is focused on the discussion of non-canonical structures found in the corpus with regards to their function in context of academic prose.
Rhematizace užitím nekanonických struktur
Keywords: rhematizace; nekanonické struktury; aktuální členění větné; rhematization; non-canonical structures; functional sentence perspective